INTERFERENSI LEKSIKAL PADA CHANNEL YOUTUBE GITA SAVITRI DALAM VIDEO 'BEROPINI' EPISODE 77: "INSECURE MULU HOW TO DEAL WITH IT" - Alza Cecaria; Sinta Rosalina (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
This study aims to find out how the form of lexical interference contained in Gita Savitri's video entitled "Opinions episode 77: 'Insecure Mulu...How To Deal With It'. The method used in this research is a qualitative research with a descriptive approach. The subject used in this study is one of the videos contained in Gita Savitri's YouTube channel and the object in this study is the use of two languages ​​used by Gita Savitri to convey her ideas and then the forms of language errors that occur in the video will be analyzed. The following: The form of lexical interference based on word class found in Gita Savitri's video entitled "Insecure mulu how to deal with it" was found as many as 59 data including nine classes of verbs, twenty-two classes of adjectives, twenty-one classes of nouns, four classes of pronouns and three classes of numerals.